2017
DOI: 10.3390/ma10080894
|View full text |Cite
|
Sign up to set email alerts
|

Sc-Decorated Porous Graphene for High-Capacity Hydrogen Storage: First-Principles Calculations

Abstract: The generalized gradient approximation (GGA) function based on density functional theory is adopted to investigate the optimized geometrical structure, electron structure and hydrogen storage performance of Sc modified porous graphene (PG). It is found that the carbon ring center is the most stable adsorbed position for a single Sc atom on PG, and the maximum number of adsorbed H2 molecules is four with the average adsorption energy of −0.429 eV/H2. By adding a second Sc atom on the other side of the system, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 44 publications
0
20
0
Order By: Relevance
“…As shown in Table 1 on 1B/PG, adsorption sites were named 1, 2, 3, 4, 5, and 6, which represented the hole position of the C ring, C-C bridge, half C ring hole position, large hexagon hole position, C top position and B top position. Results indicated that position 1 was the most easily adsorbed position of a single Sc atom on B-PG, which was similar to the situation of the undoped-PG adsorbing Sc atom [42]. The optimized geometry is shown in Figure 2a.…”
Section: Resultsmentioning
confidence: 69%
See 3 more Smart Citations
“…As shown in Table 1 on 1B/PG, adsorption sites were named 1, 2, 3, 4, 5, and 6, which represented the hole position of the C ring, C-C bridge, half C ring hole position, large hexagon hole position, C top position and B top position. Results indicated that position 1 was the most easily adsorbed position of a single Sc atom on B-PG, which was similar to the situation of the undoped-PG adsorbing Sc atom [42]. The optimized geometry is shown in Figure 2a.…”
Section: Resultsmentioning
confidence: 69%
“…Simultaneously, the B-PG plane was slightly deformed, and the adsorption energy of the Sc atom on the B-PG was −4.004 eV. In our previous study, the adsorption energy of a single Sc atom on clean PG was −2.143 eV [42], which was much smaller than that of single Sc on B-PG of −4.004 eV. It can be seen that B doping can enhance the adsorption activity of the system; compared with pure porous graphene, the Sc atom was closer to the substrate and therefore had greater binding energy on the B-doped PG.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The average adsorption energy of Li atom on β 12 -borophenec [ 32 ] is defined as: where , and are the total energy of the n Li- β 12 -borophene with i , i − 1 H 2 molecules and β 12 -borophene with n Li atoms, respectively. , and are the total energy of the β 12 -borophene, free Li atom and an isolated H 2 , respectively.…”
Section: Methodsmentioning
confidence: 99%